Reflectance and ultraviolet spectroscopy: predicting the relative growth of Saccharomyces cerevisiae in pine biomass. Issue 2 (7th February 2019) - Girelli, Gilberto Carlos; Cordeiro, Marcelo Eduardo; Nicolini, Jaqueline; Nicolini, Keller Paulo
Abstract: Ultrasound treatment favors enzymatic attack on vegetal materials and influences biological activity. The objective of this study was to develop substrates for Saccharomyces cerevisiae based on the hydrothermal treatment and ultrasound treatment of pine needle biomass. The samples subjected to ultrasound treatment at 550 °C and 650 °C showed higher reflectance bands at around 200 nm after 80 min of ultrasound treatment and lower band gap energies associated with lower IC30 values. The hydrothermal treatment with 100 min of ultrasound treatment generated more promising materials for the use of the substrates with the eukaryotic model S. cerevisiae .